COMPARATIVE STUDY OF CADIDA ALBICANS IN IRAQ - M.sc. Iman Hadi; Haneen Raheem Mohmmed; Zahraa Hasan wadaeih; Jaafar Akeel Musa; Murtadha Zuhair Mhawish; Fatima Jasim Muhammed Hussein; Zainab Hussein Kareem (Scholar Express Journals, 2022)
Candida species are the most common opportunistic pathogens in debilitated or immunocompromised hosts and cause systemic candidiasis, which has high rates of morbidity and mortality. The study aims to compare the incidence of Candidiasis among the cities of Iraq and its prevalence and the most affected cities, as well as the comparison of the results of the injury with the neighboring countries and the rates of injury
Keywords: Cadida; Albicans; Comparative Study